The effect of learning using the seven-cycle learning strategy on the achievement of Arabic language among tenth grade female students in the Ma’an district directorate - Alzidaneen, Fatehi Mohammad Salameh (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to investigate the effect of learning using the seven-cycle learning strategy on the achievement of Arabic language among tenth grade female students in the Ma’an District Directorate. The quasi-experimental approach was used to conduct the study, the study sample consisted of (85) female students who were randomly selected from Ma’an Secondary School for Girls. Of (43) female students, who studied using the usual method, and to achieve the objectives of the study, the researcher prepared a guide for the teacher and student according to the steps of the seven-step learning strategy in teaching Arabic grammar, and an achievement test consisting of (20) paragraphs of the type of multiple choice was developed. The validity and reliability of the tool were confirmed, and the results of the study indicated that there were statistically significant differences (α ≤ 05.0) between the mean scores of the female students in the post-achievement test in favor of the experimental group Arabic.